HUBUNGAN KARAKTERISTIK IBU DENGAN STATUS GIZI BALITA DI DESA SUMUR BANDUNG KECAMATAN CIKULUR KABUPATEN LEBAK TAHUN 2013 - Husnul Khotimah; Kadar Kuswandi (Jurnal Obstretika Scientia, 2014)
Nationally there are many prevalence nutrition in infants weighing less that prevalence in 2010 in infants of 18.4% and 17.9%. Prevalence is still above the target of the National Medium-Term Development Plan for 2010-2014, which is 15% and the Millennium Development Goals by 2015, ie 15.5%. This study aims to determine the relationship of maternal characteristics with nutritional status of children in desa sumur bandung cikulur in 2013 This study used a cross-sectional design with primary data from the results of the questionnaire on the entire sample of 84 mothers with infants. The results showed that there was still a toddler with poor nutrition/lack of reach (36.9%). Expected for more health workers Toddler notice nutritional status in each work area, as the nutritional status can be affected by various factors that may affect the development of the child so as to effect the nation's competitiveness.